Effects of Adipose-Derived Mesenchymal Stem Cell-Secretome on Pyroptosis of Laparoscopic Hepatic Ischemia Reperfusion Injury in a Porcine Model - Yajun Ma; Lei Cao; Pujun Li; Zhihui Jiao; Xiaoning Liu; Xiangyu Lu; Tao Liu; Hongbin Wang (Cells)
Extensive research has been conducted on mesenchymal stem cells (MSCs) regarding their ability to modify the immune response and reduce tissue damage. Many researchers have found that the regulatory capacity of MSCs primarily comes from their secretome. As a result, there has been much interest in utilizing “cell-free” therapies as alternatives to stem cell treatments. In this study, the secretome from adipose mesenchymal stem cells (ADSC-secretome) was extracted and injected into minipigs with established liver injury models. Blood and liver tissue samples were obtained prior to the procedure, as well as on days 1, 3, and 7 after surgery. It was found that ADSC-secretome effectively suppressed the synthesis of the NOD-like receptor protein 3 (NLRP3) inflammasome, leading to a downregulation of gasdermin-D (GSDMD) expression, and demonstrated a more prominent anti-pyroptosis effect compared to ADSCs. Furthermore, ADSC-secretome inhibited the high mobility group box 1 (HMGB1)/toll-like receptor 4 (TLR4)/nuclear factor kappa-B (NF-κB) inflammatory pathway. In summary, both ADSC-secretome and ADSCs inhibited pyroptosis in right hemihepatic ischemia–reperfusion combined with left hemihepatectomy injury, and ADSC-secretome exhibited a stronger therapeutic effect. ADSC-secretome exerted these therapeutic effects through the inhibition of the HMGB1/TLR4/NF-κB inflammatory pathway. In the future, “cell-free” therapy is expected to replace cell-based methods.